TAX CULTURE AND TAX MORALE: IMPACT ON TAX COMPLIANCE IN UKRAINE - Stetsenko, Tetiana; Nishcheretov, Orest (Social Economics, 2021)
The purpose of writing this article is to assess the impact of tax culture and tax morale on the tax compliance in Ukraine and to develop recommendations for further transformation of the national tax culture. We established that among the reasons for maintaining the size of the shadow sector of the economy in Ukraine is the focus on reforming the tax system, tax administration without taking into account the tax culture that has developed historically. Components of tax culture have different levels of formation. Procedural and technological culture is currently being actively developed. Digitalization and electronic services, involvement in the international fight against tax evasion facilitated this process. The culture of behavior, primarily of taxpayers, was formed spontaneously, without the direction of the process by the authorities. Given the confirmed correlation between tax compliance and tax morale, widespread taxpayer deviant behavior in Ukraine is largely due to low tax morale. The level of tax morale in Ukraine tends to decrease and tends to minimum rather than average values in the sample of World Values Survey`s countries. We determined that the low level of tax morale in Ukraine is caused mainly by the action of institutional factors: distrust of the government, government instability, anti-democratic phenomena and corruption. In Ukraine, for further development of tax culture it is necessary to follow next recommendations: to conduct a large-scale sociological survey to identify all socio-economic and institutional factors influencing the tax morale of domestic taxpayers, as well as to identify the current level of tax literacy; actively introduce tax education at all levels of education. Further research will be related to assessing the level of tax literacy in Ukraine.